Soft Computing Techniques for Mutual Coupling Reduction in Metamaterial Antenna Array. (6th November 2013) - Choudhury, Balamati; Manickam, Sangeetha; Jha, R. M.
Abstract : Application of soft computing techniques for various metamaterial designs and optimizations is an emerging field in the microwave regime. In this paper, a global optimization technique, namely, particle swarm optimization (PSO), is used for the design and optimization of a square split ring resonator (SSRR) having a resonant frequency of 2.4 GHz. The PSO optimizer yields the structural parameters, which is further simulated and validated with the optimized value. This optimized structure results in the mutual coupling reduction in a microstrip antenna array designed for wireless application.